Synthesis And Antioxidant Activity Of Galloyltyrosine, Derivatives From Young Leaves Of Inga Laurina - B.VENKATESWARA RAO,; K. RAMANJANEYULU,; T.RAMBABU,; CH.B.T.SUNDARI DEVI, (International Journal of Pharma and Bio Sciences, 2011)
Synthesis of Galloyltyrosine and its derivatives 9a-e and 13a-c was achieved from appropriately substituted benzoic acid and L-tyrosine. While compounds 9a-e and 13a-c was exhibited potent antioxidant activity in both the NBT and DPPH – radical scavenging models among the synthesized Galloyltyrosine derivatives.